2007
DOI: 10.1017/s1751731107000031
|View full text |Cite
|
Sign up to set email alerts
|

Milk intake and carbon dioxide production of piglets determined with the doubly labelled water technique

Abstract: The present study was undertaken to study different methodological aspects of quantifying CO 2 production and milk intake of suckling piglets using the doubly labelled water (DLW) technique. In total, 37 piglets were enriched intraperitoneally with DLW to study equilibration time of 18 O (n 5 3), to validate the estimation of milk intake and CO 2 production (n 5 10) of piglets fed milk replacer and to quantify milk intake and CO 2 production of piglets nursed ordinarily by sows (n 5 24). Enrichment of 18 O in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The estimated feed intakes are shown in Table 2. 1 Based on averages of days 10-13 and days 17-20 [12]. 2 Based on the average supplementation at days 10, 17, and 24.…”
Section: Nutrient Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…The estimated feed intakes are shown in Table 2. 1 Based on averages of days 10-13 and days 17-20 [12]. 2 Based on the average supplementation at days 10, 17, and 24.…”
Section: Nutrient Uptakementioning
confidence: 99%
“…Several studies have suggested that, in addition to age, the main driver for gut maturation is dry matter (DM) intake rather than a specific nutrient composition [ 12 ]. In some conventional pig production systems, creep feed is provided to accommodate the piglets to a vegetable-based diet prior to weaning, thereby potentially also increasing the activity of certain disaccharidases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is also evident that homemade milk replacers previously used in research (Kim & Wu, ; Yao et al., ) are suboptimal when comparing fat, protein and energy content and amino acid composition of the one used in the present study with the composition of the sow milk analysed (Table ). Thus, when daily amount of milk consumed does not differ between artificially reared and suckling piglets, it would naturally result in greater ADG of suckling piglets (Theil et al., ). However, despite the suboptimal milk replacer diet applied in this study, artificial rearing resulted in similar weaning weight when compared with conventionally reared piglets with similar birthweight (6.3 vs. 6.7 kg).…”
Section: Discussionmentioning
confidence: 99%
“…Applying milk replacer to early-weaned piglets has been shown to improve daily gain of medium and heavy birthweight piglets (Zijlstra, Whang, Easter, & Odle, 1996), suggesting it to be a viable alternative to insufficient sow milk yield. However, one important disadvantage of available commercial milk replacers is the suboptimal nutrient and amino acid composition compared with the sows' milk (Mavromichalis, Parr, Gabert, & Baker, 2001;Theil, Kristensen, Jorgensen, Labouriau, & Jakobsen, 2007). Being important for growth (Kim & Wu, 2004), the semi-essential amino acid arginine (ARG) is involved in the protein synthesis signalling pathway of the mammalian target of rapamycin (mTOR) (Yao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in the laying hen, steer, and dairy cow studies, the modeled CO 2 production rates had little variation due to stable body weights during the experiments. Most of the variation in the measured CO 2 production rates in these studies was not captured by the model, although average values of the Pederson et al, 2008;Zheng et al, 2006;Zhao et al, 2001;Pedersen and Thomsen, 2000;Jørgensen et al, 1996b;Jørgensen et al, 1990. [c] Pederson et al, 2008;Eerden et al, 2006;Li et al, 2005;Parmentier et al, 2002;Mashaly et al, 2000. [d] Bolhuis et al, 2008;Pederson et al, 2008;Hansen et al, 2007;Jørgensen et al, 2007;Theil et al, 2007;Blanes and Pedersen, 2005;Chwalibog et al, 2004;Sousa and Pedersen, 2004;Wang et al, 2004;Gerrits et al, 2001;Jørgensen et al, 2001;Jørgensen, 1998;Jørgensen et al, 1997;Jørgen-sen et al, 1996a;Jørgensen et al, 1996c. [a] (2) Modeled CO 2 Production Rates (mL s -1 head -1 ) [a] (2)/(1) [a] Values are means ± standard deviations.…”
Section: Comparison Of Measured and Modeled Vrmentioning
confidence: 99%